Use of Evidence-Based Management in Public Hospitals Management in Iran: A National Survey - Edris Hasanpoor; Ali Janati; Masumeh Gholizadeh; Elaheh Haghgoshayie (Tehran University of Medical Sciences, 2018)
Background: Evidence-based Management (EBMgt) has been developed as a management model to improve the quality of management decisions. Hospital managers' decisions can have a significant impact on service effectiveness and hospital success. Hence, this study aimed to survey sources of evidence among public hospitalschr('39') managers for decision-making in Iran.   Materials and Methods: This cross-sectional study was conducted with 183 managers of public hospitals in eight educational centers of the Ministry of Health and Medical Education in 2017. The research tool was an evidence-based management questionnaire with 20 items and 6 main domains. Data analysis was performed using descriptive and inferential tests by SPSS21.   Results: One hundred seventy-two (94%) out of 183  participants were male. The mean age and work experience were 45.28 and 19.30 years, respectively. The lowest score was related to "the academic journals" (52.56%), While managers relied heavily on "Ministry of Health programs" (80.98%). The average use of scientific-research evidence, fact and hospital information, political-social development plans, managers' professional expertise and ethical-moral evidence and values and expectations of all stakeholders were 59.70%, 62.43%, 75.30%, 71.36%, 71.83% and 73.7%, respectively.   Conclusion: The study results revealed that hospital managers utilized the scientific-research evidence less than other evidence, which it is a matter of concern; so, managers need to improve their education and research level. Using hexagon of evidence sources, managers can identify the best available evidence for hospital decisions and they make the best decision in the process of evidence-based decision making.